Vermiconversion of paper industry waste for recycling the nutrients usig earthworm eudrilus eugeniae kingberg on growth of cluster bean (cymopsis tetragonoloba) - Sivakumar, P.; Chithra, R. (International Journal of Biological Research, 2016)
Objective: To preparation of vermicompost from paper industry waste for recycling the nutrients using earthworm Eudrilus eugeniae kingberg. To analyze the physico chemical parameters of vermicompost, vermiwash and vermicompost extract, enumeration of microorganism from vermicompost, growth parameters and biochemical characteristics of Cluster bean (Cymopsis tetragonoloba) were studied.Methods: The paper industry wastes washed for two times with preparing the predecompost and it kept in 30 days. For preparing the vermicompost, the predecomposition was directly mixed with cowdung in the ratio of 1:2 on dry weight basis in same tank. Seventy number of healthy, clitellate Eudrilus eugeniae kingberg were introduced in the same tank. After 45 days the trial tank compost were sieved and collected for paper industry waste vermicompost.Results: The physico chemical parameters of vermicompost vermiwash and vermicompost extract were studied, the growth parameters and biochemical characteristics were higher in treatments 5 and 6 of Cluster bean were using various concentration of vermicompost, vermiwash and vermicompost extract.Conclusion: Present study was concluded that the Eudrilus eugeniae kingberg is more efficient in bioconversion of paper industry waste vermicompost, vermiwash and vermicompost extract were using various concentration of pot culture study of brinjal was higher growth and high yield and vermicompost act as an excellent biofertilizer of crop plants.
Keywords: Vermicompost; Vermi Wash; Vermicompost Extract; Physico Chemical Parameters; Growth and Biochemical Parameters.